Assessment of the salivary level of glutathione and the feeding pattern in molar incisor hypomineralization among 7-9 years of age: an analytical cross-sectional study - Alaa H Salih; Alhan A Qasim; Jafar Kolahi (College of Dentistry/ University of Baghdad, 2024)
Background: The study aimed to assess salivary glutathione levels and the pattern of feeding on molar incisor hypomineralization among healthy children aged 7-9 years. Materials and Methods: The study was a cross-sectional study. A total of 90 children sample was further sub classified into two groups: the study group, including 60 children with molar incisor hypomineralization, classified into two subgroups, 30 children with mild type and 30 children with severe type of molar incisor hypomineralization. In addition to the control group involving 30 children without incisor hypomineralization and free of caries. Examination and diagnostic criteria for hypominerlization of the molar incisor and assessment of severity were according to European Academy of Pediatric Dentistry (EAPD) guidelines in 2003. The salivary glutathione ELISA kit was used to assess the amount of glutathione in unstimulated saliva samples. After an oral examination, the parents of each child completed a self-administered questionnaire that included information on the child's feeding pattern during the first year of life. The questionnaires were returned to the researcher the following day. The child who received a mixed feeding pattern was excluded from the study. Results: The ordinal logistic regression model (Overall model test: p < 0.001) presented that salivary glutathione (p < 0.001), saliva pH (p = 0.014) and saliva flow rate (p = 0.009) were significant predictors of hypomineralization of the molar incisor. The feeding pattern (p = 0.625) and gender (p = 0.394) were not significant predicators for hypomineralization of the molar incisor hypomineralization. Conclusion: In children aged 7 to 9 years, salivary glutathione level is a negative predicator for the degree of hypomineralization of the molar incisor. Moreover, child feeding pattern, and gender, are not significant predicators of hypomineralization of the incisor hypomineralization.